MENEJEMEN SUMBER DAYA MANUSIA DI PERPUSTAKAAN - S. Komarudin, Yooke Tjuparmah; Dewi, Laksmi (Edulib, 2012)
The era in which the exstense of ICT brings with it enlightenment in every aspect of life changes of paradigms in libraries exists. The change includes a transfer in system – from conventional type of services to ICT-based services with some orientation for the sake of users’ needs. The innovations taking place in libraries are influenced by 10 issues: "... a) the presence of electronic paper, b) new publishing model, c) on-line bookstore, d) e-commerce, e) digital television, f) integrated learning environment , g) remote university, h) mobile communication, i) print-on-demand, j) the threat og the unknown". The change in paradigms leads to manajerial which formely management bound to merely build and develop library collection, product-oriented services of information to ICT-based services management. Three major ICT-based services comprise human resources and non human resources, proactive kind of services and users empowerment. Accordingly, libraries an entitiy need to be managed bt human resources with managerial competence (leading, planning, organizing dan controlling), bibliograpical and library technological know-how, human relation skill, ability to work in team, elite type of conduct, elegance and intelligence, being ordered, ordered, school curriculum, writing competency, publishing, users needs, work partnership, ability of reading publisher’s catalog both printed and online, desoiderata, budgeting, statistics, accesion list, registration book, classification, catalouging both manually and in an electronic mode, indexing, writing an abstract, accessories, shelving, binding, fumigation, camouflaging, and others), services competency, users-oriented services, users empowering, wide horizons, expertise in one field of dicipline, knowledge of principles and techniques in guidance and counseling, social sciences, psychology and culture, library technological know-how, communication skill, human resources skill, emphaty, attractive appearance, fair, helpful, information and science know-how, form-making skil, flow charts of services, organizing materials, guides/labels, rules and policy, correspondency, shelving,PERPUSTAKAAN reporting/evaluating/statistic, punishment, how to use library education, simple general infromation, good sense of media, answeing reference questions skill, helping people to obtain information through face to face contact, assistance to readers in searching information, bibliographical searching/service, and competency and ICT (the use of hardware and implementing of all softwares on all operational activities in the library). The competency of human development at schools/madrasah should refer to Act #43/2007 on Library and the Ministry Regulations #25/2008 on Standard of School Librarians.